Efektifitas Perbandingan Leaflet Dan Video Edukasi Terhadap Pengetahuan WUS Tentang Pemeriksaan IVA Test - Purwanti, Rita; Wiyadi, Wiyadi; Raihanah, Siti (Bunda Edu-Midwifery Journal (BEMJ), 2023)
The impact of the lack of interest in WUS in the IVA TEST causes an increase in the prevalence of cervical cancer in women every year as evidenced by some of the exposed data.The purpose of this study was to determine the effect of the effectiveness of the comparison of leaflets and educational videos on WUS knowledge about the importance of the IVA Test in public health center Bangun City in 2023. Method the research Type of quantitative research with the Pre-experimental design method, with the one group pretest-posttest design. The population is all WUS in 2023 in the working area of the Kota Bangun Health Center, totaling 30 respondents obtained by total sampling. The data collection instrument was a questionnaire, data analysis using the Wilcoxon and Mann Whitney tests. Univariate analysis found that most of the respondents were aged 30-34 years, most had jobs, most had high school/MA education, and most had a number of children. Bivariate analysis of the Wilcoxon test showed a p value = 0.001 (p > 0.05 ) on leaflet media and p value = 0.002 (p > 0.05) on video media. This shows that there is effectiveness between leaflets and educational videos on WUS knowledge about the IVA Test examination, the two variables are different, meaning that video media is more effective than leaflets in increasing WUS knowledge. Cervical cancer is the most common type of malignancy among women. As a result of the lack of knowledge and lack of information causing fear to carry out examinations, efforts to increase mother's knowledge need to be socialized about the importance of IVA tests with health promotion.